2020
DOI: 10.1186/s12913-020-05574-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and reporting patient participation by means of patient preferences and experiences

Abstract: Background: Although patient participation is strongly associated with high quality of healthcare, valid means to measure and report a comprehensive notion of patient participation are scarce. The Patient Preferences for Patient Participation (4Ps) is a new healthcare practice and research tool, comprising patients' preferences as well as experiences. The 4Ps employs 12 items for the patient to conceptualise patient participation. The aim of this paper is to describe how the two perspectives of patient partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 37 publications
2
42
0
Order By: Relevance
“…The findings show a high overall degree of match between patients' preferences and experiences in terms of patient participation, especially for items such as being listened to by professionals and/or managing one's treatment. Supposedly, this indicates that the patients' engagement aligns with the conditions for participation that they, as individuals, favour 28 . This could indicate that each individual's varying needs are recognised and acknowledged by the healthcare services 2…”
Section: Discussionmentioning
confidence: 99%
“…The findings show a high overall degree of match between patients' preferences and experiences in terms of patient participation, especially for items such as being listened to by professionals and/or managing one's treatment. Supposedly, this indicates that the patients' engagement aligns with the conditions for participation that they, as individuals, favour 28 . This could indicate that each individual's varying needs are recognised and acknowledged by the healthcare services 2…”
Section: Discussionmentioning
confidence: 99%
“… 1 Yet, previous studies have shown that the conditions are far from optimal for preference‐based patient participation and that further efforts are needed to create an enhanced and person‐centred standard. 31 , 34 , 40 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…Further, IF teams and managers will be asked to keep notes, by means of an individual, semi-structured reflective diary [ 42 ]. Structured patient record assessment in triangulation with a post-discharge structured survey to all hip surgery patients for voiding difficulties after the hospital episode, self-care management and conditions for participating in accordance with one’s preferences—the latter using the 4Ps tool (Patient Preferences for Patient Participation) [ 43 45 ]. Further, data will originate from qualitative interviews with a sample of two patients per data collection point and site, representing the age range and gender distribution among those having had hip surgery.…”
Section: Methodsmentioning
confidence: 99%